(untitled) (World Economics and Finance Bulletin, 2026)
The rapid expansion of green bonds positions sustainable finance at the core of climate mitigation strategies. However, empirical evidence on their crisis resilience and corporate value effects remains contradictory. This study synthesizes 73 peer-reviewed articles using meta-analytical methods (randomeffects models, FAT-PET, PEESE) to resolve these discrepancies. We propose and test the Asymmetric Shock Resilience Hypothesis: green bonds exhibit diametrically opposite behaviors depending on shock origin